Nuclear South Asia: How it is different from Cold War - Ms. Maryam Zubair (CISS Insight Journal, 2017)
Three significant developments marked the end of the WWII and defined the post-war international system: the emergence of the United States and the Soviet Union (USSR) as the two superpowers in a bipolar structure of international system, the birth of the United Nations, and most importantly, the introduction of nuclear weapons as a tool in inter-state relations. With the establishment of the UN, the world powers set out to create a platform where states could work out problems that could potentially destabilize the international system. It was under the spirit of this initiative that the perils that accompanied the advent of nuclear weapons were addressed. Though characterized by extreme competition between the two super powers, the Cold War was punctuated by bilateral talks and efforts at multilateral forums like the UN to maintain the stability of the international system. State to state communication remained an important feature of the Cold War, even in the adversarial environment, between the two strategic competitors. The Cold War also introduced new meanings to the terms strategy and deterrence. These terms became specific to nuclear weapons. A few more states also acquired nuclear weapons, as the usefulness of the atomic bomb, and the relationship between possession of atomic weapons, state power and prestige were better understood. Concepts associated with deterrence in the first nuclear age1 (1945-1991) remained relevant in the second nuclear age, when other powers acquired nuclear weapons.